1999
DOI: 10.1063/1.478692
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic-energy dependence of competitive spin-allowed and spin-forbidden reactions: V++CS2

Abstract: The kinetic-energy dependence of the V++CS2 reaction is examined using guided ion-beam mass spectrometry. Several different ion sources are used to systematically vary the V+ electronic state distributions and elucidate the reactivities of both the ground and excited state V+ cation. The cross section for VS+ formation from ground state V+(5D) exhibits two endothermic features corresponding to the formation of ground state VS+(3Σ−) and excited state VS+(5Π). The thresholds for these two processes are in good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
112
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 51 publications
16
112
0
Order By: Relevance
“…In such cases, an additional E Ϫ1/2 factor needs to be introduced such that m is effectively 1.5. As discussed in detail in our most recent work [29], this expression can be justified by appealing to a Landau-Zener model [31,32] and agrees with several modern theoretical treatments [33,34] for the kinetic energy dependence of the crossing probability between diabatic surfaces of different spin multiplicities.…”
Section: A Simple Model For the Kinetic Energy Dependence Of Reactionssupporting
confidence: 77%
See 1 more Smart Citation
“…In such cases, an additional E Ϫ1/2 factor needs to be introduced such that m is effectively 1.5. As discussed in detail in our most recent work [29], this expression can be justified by appealing to a Landau-Zener model [31,32] and agrees with several modern theoretical treatments [33,34] for the kinetic energy dependence of the crossing probability between diabatic surfaces of different spin multiplicities.…”
Section: A Simple Model For the Kinetic Energy Dependence Of Reactionssupporting
confidence: 77%
“…However, we [28,29] and others [30] have documented exceptions to this conclusion associated with reactions that are limited by coupling between reaction surfaces of different spin. In such cases, an additional E Ϫ1/2 factor needs to be introduced such that m is effectively 1.5.…”
Section: A Simple Model For the Kinetic Energy Dependence Of Reactionsmentioning
confidence: 58%
“…61 On the other hand, from a fundamental point of view, the chemical reactivity of transition metal oxides is strongly influenced by the availability of multiple low-lying electronic states in these species. 31,62,63 This means that the reactions involve several electronic states that may also have different spins, namely, it should involve spinconserving and spin-inversion processes.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of reaction types such as coordination, insertion, etc., which have been studied both experimentally and theoretically [5]. Studies by Jiang and Rue et al [1,6] have calculated for the reactions of V + (Fe + ) and CS 2 , and found that they proceed via an insertion-elimination mechanism. As for the reactions of a transition metal ion with SCO, this was observed to be more complicated as a consequence of the molecule having both a C-S bond and a C-O bond.…”
Section: Introductionmentioning
confidence: 99%